Clinical Differences between Early- and Late-Onset Asthma: A Population-Based Cross-Sectional Study. (12th January 2021) - Li, Jiaming; Ye, Ling; She, Jun; Song, Yuanlin
Abstract : Background . Limited information exists about the nature of late-onset asthma (LOA) without medication intervention when compared to early-onset asthma (EOA). Our goal was to understand how EOA and LOA affect clinical and pathophysiological features. Methods . A population-based cross-sectional study was carried out in Zhongshan Hospital (Shanghai, China). EOA and LOA were based on age of diagnosis (before and after age 40 years, respectively). Clinical variables were collected with an emphasis on allergic features, analyzed, related, and compared using one-way ANOVA or Kruskal-Wallis test. Correlations between blood basophils and clinical data were evaluated by Spearman's rank test. Statistical analyses were conducted with SPSS v24.0. Results . Of a total of 12, 760 adults with cough, sputum, or chest tightness, 90 subjects with EOA (mean age ± standard deviation (SD):28.73 ± 5.89), 111 with LOA (mean age ± SD: 60.25 ± 9.85), and 106 with chronic obstructive pulmonary disease (COPD) (mean age ± SD: 61.58 ± 10.95) were selected. FEV1 /FVC (%), FEV1 % predicted, and FVC% predicted were all significantly lower in LOA compared to EOA p < 0.01 . The values of post-bronchodilator FEV1 in bronchodilator reversibility testing were higher in the LOA and EOA groups compared to subjects with COPD p < 0.01 . Among allergic features, mite sensitization was most common in EOA patients, followed by LOA and COPD, whereas mold sensitization was more prevalent in LOA than EOA. Moreover, blood eosinophils were a typical feature of asthma in both EOA and LOA compared to COPD and controls p < 0.01, and there were no differences in blood neutrophils in LOA compared to controls. Interestingly, blood basophils were increased in both EOA p < 0.01 and LOA p < 0.05 compared to COPD and controls. This variable correlated with eosinophils in EOA ( r = 0.549, p = 0.002 ) but not in LOA. Conclusion . LOA is a distinct clinical entity from EOA. In LOA, atopy was less frequent and spirometry values were lower when compared to EOA. In EOA, blood basophils and eosinophils were significantly correlated owing to pathophysiological differences between the two forms of the disease.